Zishen Yutai Pills Promote Angiogenesis at the Maternal-Fetal Interface in Recurrent Spontaneous Abortion Mice by Regulating miR-187/VEGF Axis - Wang X; Hu H; Yu X; Liang C; Han Y; Chen H; Chu J (Dove Medical Press, 2024)
Xiaoli Wang,1,* Heng Hu,1,2,* Xinhui Yu,1 Chengcheng Liang,1 Yanquan Han,1 Hongxia Chen,1 Jijun Chu1 1The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui, 230031, People's Republic of China; 2Anhui University of Chinese Medicine, Hefei, Anhui, 230038, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongxia Chen; Jijun Chu, Department of Gynaecology, the First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, People's Republic of China, Email 13305690727@163.com; chujijun8888@163.comEthnopharmacological Relevance: Zishen Yutai pills (ZYP), a traditional Chinese patent medicine, was listed in China in 1981. It is composed of 15 traditional Chinese medicines and has the effects of regulating menstruation, helping pregnancy, and preventing abortion. In clinical practice, it is effective in preventing habitual and threatened miscarriages, and continuing to explore its mechanism of action is very meaningful research.Aim of the Study: To explore the possible mechanism of ZYP promoting angiogenesis at the maternal-fetal interface in recurrent spontaneous abortion (RSA).Materials and Methods: In vitro experiments, placental trophoblast cells (PTCs) were isolated from the placental tissue of RSA mice and divided into six groups: Control group, Model group, ZYP group, miR-187 inhibitor NC group, miR-18 7 inhibitor group, and miR-187 inhibitor+ZYP group. Cell viability and cell cycle were measured using CCK8 and flow cytometry, respectively. The expression levels of miR-187, VEGF, VEGF-R1, and VEGF-R2 were measured using RT-qPCR, WB, and IF staining. Animal experiments first establish an RSA mice model (CBA/J × DBA/2) and then randomly divide the mice into four groups (n=10): normal pregnancy group, RSA model group, ZYP group, and progesterone capsule group. Observed the changes in embryo absorption rate, pathological morphology of decidual tissue, and ultrastructure of vascular endothelial cells in each group of mice. RT-qPCR, WB, and IF staining methods were used to determine the expression of miR-187, VEGF, VEGF-R1, and VEGF-R2.Results: In vitro, ZYP promoted the viability of PTCs and regulated their cell cycle, and ZYP down-regulated miR-187, up-regulated VEGF, VEGF-R1 and VEGF-R2 levels. miR-187 inhibitor showed the same effects, and further ZYP intervention enhanced the effects. In vivo, ZYP remarkably reduced embryo resorption rates, and improved the pathological morphology of decidual tissues and ultrastructure of vascular endothelial cells. Moreover, ZYP down-regulated miR-187, up-regulated VEGF, VEGF-R1 and VEGF-R2.Conclusion: In summary, ZYP can regulate the expression of VEGF via miR-187, then promote the angiogenesis at the maternal-fetal interface, and playing a therapeutic role in RSA. Keywords: recurrent spontaneous abortion, Zishen Yutai pills, miR-187, vascular endothelial growth factor, VEGF, angiogenesis